PRESPEKTIF MAQASHID SYARIAH : PERAN EKONOMI HIJAU DAN BIRU DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS - Eny Latifah; Rudi Abdullah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Economic governance manages by maintaining and maintaining the use of the environment in a green economy and blue economy which will encourage the government to realize the sustainable development of a country. Research using a descriptive method of this type of literature has the aim of knowing the role of the green and blue economy in realizing sustainable development. The results of the study show that the role of the green and blue economy in realizing sustainable development is (1) realizing community welfare through the approach of partnership, institutional, fisheries and tourism, and entrepreneurship aspects; (2) reducing poverty, carbon dioxide emissions, and ecosystem degradation; (3) increasing human well-being and reducing inequality through activities that do not expose future generations to significant environmental risks and ecological scarcity; (4)